Women’s survey instrument on voice and agency in local governance in Nigeria - Adida, Claire; Arriola, Leonardo; Fisher, Rachel; Kosec, Katrina; Kyle, Jordan; Matanock, Aila; Mo, Cecilia H.; Adeyanju, Dolapo; Olanrewaju, Opeyemi (International Food Policy Research Institute, 2023)
This questionnaire was prepared by IFPRI. It is part of the CGIAR Research Initiatives on Gender Equality (HER+) and Fragility, Conflict, and Migration (FCM). It also benefitted from funding from the CGIAR Gender Impact Platform. We would like to thank all funders who supported this research through their contributions to the CGIAR Trust Fund: https://www.cgiar.org/funders.